2009
DOI: 10.1088/0022-3727/42/11/115301
|View full text |Cite
|
Sign up to set email alerts
|

Au+and Au3+ions in CeO2rf-sputtered thin films

Abstract: The interaction of gold with CeO2 layers was investigated using photoelectron spectroscopy. 65 nm thick Au doped CeO2 layers were deposited by rf-magnetron sputtering on a Si(0 0 1) substrate by using a composite CeO2–Au target. The laboratory XPS and synchrotron radiation soft x-ray and hard x-ray photoemission spectra showed the formation of stoichiometric Ce4+ (CeO2) and the appearance of new Au+,3+ states with ionized Au species in excess of 50% of the total Au amount. Depth resolved measurements, by varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
5
32
0
1
Order By: Relevance
“…The formation of ionic species is typically found for films prepared by magnetron co-sputtering of CeO 2 in combination with transition metals. 40,49,50 The ratio between the Pt 2+ , Pt 4+ , and Pt 0 contributions in the Pt 4f is a function of the sampling depth. Accordingly, Pt 4+ species are located mostly in the bulk while Pt 2+ and Pt 0 reside at the surface.…”
Section: High Efficiency At Ultra-low Noble Metal Loadingmentioning
confidence: 99%
“…The formation of ionic species is typically found for films prepared by magnetron co-sputtering of CeO 2 in combination with transition metals. 40,49,50 The ratio between the Pt 2+ , Pt 4+ , and Pt 0 contributions in the Pt 4f is a function of the sampling depth. Accordingly, Pt 4+ species are located mostly in the bulk while Pt 2+ and Pt 0 reside at the surface.…”
Section: High Efficiency At Ultra-low Noble Metal Loadingmentioning
confidence: 99%
“…This means that the depth into the sample from which these electrons escape is similar for each element. By selecting more than one photoelectron energy it is possible to get some information about the depth distribution of elements or chemical species 13–19. This technique is known as energy resolved XPS (ERXPS) depth profiling.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that cosputtering of cerium oxide with gold led to a formation of a new type of a thin film catalyst with high concentration of ionic gold in Au +,3+ states. [5] Similarly, Pt-doped cerium oxide films prepared by rf sputtering exhibit an unusually high concentration of cationic platinum Pt 2+ and Pt 4+ (nearly 100%) which opens the way for using such systems as highly active thin film catalysts. When used as an anode material in hydrogen-fed polymer membrane fuel cell (PMFC), Pt-CeO 2 films deposited on carbon nanotubes (CNTs) exhibits very high specific power (W/mg Pt) showing that such material represents a promising alternative catalyst for fuel cell applications.…”
Section: Introductionmentioning
confidence: 99%